Child Gender Dysphoria: An Ethical Reflection on Vulnerability, Responsibility and Benefits in Colombia (Revista Iberoamericana de Bioética, 2020)
To speak of child gender dysphoria in Colombia is to confront the vacuum in this area, owing to, among other things, to cultural factors and heterodomination. Until very recently, the country was in the very early stages of looking at, and working on, on the theme of gender diversity. The research we address here is intended as a contribution that might serve to establish paths in this specific field of knowledge for future research in Colombia.
Keywords: dysphoria; children; school; gender; ethics